2018
DOI: 10.1002/2017jc013640
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Mixed‐Layer Salinity Seasonal Variability in the Indian Ocean

Abstract: Based on a joint analysis of an ensemble mean of satellite sea surface salinity retrievals and the output of a high‐resolution numerical ocean circulation simulation, physical processes are identified that control seasonal variations of mixed‐layer salinity (MLS) in the Indian Ocean, a basin where salinity changes dominate changes in density. In the northern and near‐equatorial Indian Ocean, annual salinity changes are mainly driven by respective changes of the horizontal advection. South of the equatorial reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…The role of horizontal advection can also be emphasized by a pattern of diagonal alignments of local maxima and minima in the Hovmoller plot of seasonal SSS anomaly (Figure 6b, yellow arrow), which reflects seasonal changes in the SCS circulation. Overall, the balance of seasonal SSS in the SCS appears to be very delicate and should involve all the terms in the MLS budget (Kohler et al., 2018). Such a detailed analysis is, however, beyond the scope of the present study and is referred to a future study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of horizontal advection can also be emphasized by a pattern of diagonal alignments of local maxima and minima in the Hovmoller plot of seasonal SSS anomaly (Figure 6b, yellow arrow), which reflects seasonal changes in the SCS circulation. Overall, the balance of seasonal SSS in the SCS appears to be very delicate and should involve all the terms in the MLS budget (Kohler et al., 2018). Such a detailed analysis is, however, beyond the scope of the present study and is referred to a future study.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the balance of seasonal SSS in the SCS appears to be delicate, with different terms dominating regionally, and should likely involve all the terms in the mixed layer salt budget. This might be difficult to evaluate using available observational data though (Kohler et al., 2018). Also, the factors controlling patterns of seasonal SSS distribution appear to be closely related to the SCS monsoon system; thus, any changes in the monsoon climate (e.g., related to the ENSO) can affect the seasonal cycle of SSS in the SCS as well.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…They found that these discrepancies are caused by cumulative effects of high‐frequency variability, which cannot be accurately sampled by a monthly time resolution. Given that vigorous high‐frequency variability also exists in the tropical IO (Schott et al, ), and its rectification substantially contributes to the seasonal cycle of the upper ocean temperature (Duncan & Han, ) and salinity (Köhler et al, ) there and interannual variability of the eastward surface jets that transport salty water from the Arabian Sea to the eastern IO (Han et al, ), it is desirable to revisit the validity of mechanisms responsible for the pIOD‐related salinity anomalies through an online salinity budget analysis that allows exact closure of the salinity budget. The key questions of this study are as follows: To what extent are the processes proposed by previous studies appropriate?…”
Section: Introductionmentioning
confidence: 99%
“…In addition to typical output like temperature, salinity, and velocity, six terms concerning salinity change rate related to the contribution of advection and diffusion in the U , V , W directions are conducted separately. Terms estimated from monthly outputs may differ significantly from those directly outputted by an online calculation, especially when high-frequency changes occur (Hasson et al, 2013;Köhler et al, 2018). This so-called "online analysis" avoids the problem of large residuals when directly using monthly data and allows us to precisely close the salinity budget and track relevant exchange processes of salinity.…”
Section: Model Settingmentioning
confidence: 99%